The Crime of Theft in the Kutaramanawadharmasastra: Perspective of the Purpose of Punishment - Utami, Tanti Kirana; Putri Rizdyani, Kayla; Adzani, Hilda Mahardika; Suntio, Myllania Willia; Qolbi, Ramdania Shophiatul (Indonesian Journal of Law and Justice, 2025)
This research discusses the regulation of the crime of theft in Kutaramanawadharmasastra-a traditional Hindu law book that has a great influence on the legal system of the Majapahit Kingdom-in the perspective of the purpose of punishment. The focus of the study is directed at normative and philosophical analyses of the forms of sanctions imposed, as well as their relevance to the modern punishment system in Indonesia. The main objective of this research is to explore the values of substantive justice and local wisdom contained in the Kutaramanawadharmasastra, as well as to consider its potential as a reference in national criminal law reform. The method used is normative juridical approach with the support of secondary data through literature study, as well as empirical juridical approach to examine the context of law application in the past. The results showed that the book contains principles of punishment that are not only repressive but also restorative, such as restitution and social recovery. Although there are caste-based discriminatory aspects in the sanction system, some elements such as the obligation to compensate, restoration of social relations, and protection of property rights remain relevant and can be selectively adopted in today's restorative justice framework. This research confirms the importance of reflecting traditional legal values to enrich Indonesia's pluralistic legal system, as well as part of the effort to build a more humanistic, contextualised and nationalised punishment system.